The 1990 Reform of United Kingdom Local Authority Finance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
In April 1990, the U.K. Government implemented the largest change to local authority finance in England and Wales since the postwar period. It involves the introduction of a poll tax on domestic residents, the centralization of local business taxes, and an overhaul of Central Government grants. This paper analyzes the effect of these reforms on local government and the wider economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet